2019
DOI: 10.1080/16878507.2019.1654658
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gamma radiation on some biological aspects and ultrastructure of female ovaries of the house fly, Musca domestica L. (Diptera: Muscidae)

Abstract: The present study aimed at evaluating the effect of lethal doses of gamma radiation (LD 25 , LD 50 and LD 75) on reproductive potential of females resulted from irradiated pupae, and the latent effect on first generation (F1). In addition, ultrastructure alterations in resulted female ovaries were studied using transmission electron microscope. The numbers of eggs laid were 158.3 and 70.0 eggs/5♀♀♀ at LD 25 and LD 50 , respectively, compared with 536.7 eggs/ 5♀♀ for control, and while no eggs were deposited by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
(16 reference statements)
1
2
0
Order By: Relevance
“…Also, the present study showed that sterility ofC. albicepswas increased with increasing dose to reach 100.0 % at 20 Gy; similar results were obtained by Donnelly (1960) for Lucilia sericata, Crystal (1979) for Coclio hominivorax, Karunamoorthy and Lalitha, (1987) for L. cuprina, Huda andKhan, (2000) L. cuprina andHassan et al,(2019) for Musca domestica.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Also, the present study showed that sterility ofC. albicepswas increased with increasing dose to reach 100.0 % at 20 Gy; similar results were obtained by Donnelly (1960) for Lucilia sericata, Crystal (1979) for Coclio hominivorax, Karunamoorthy and Lalitha, (1987) for L. cuprina, Huda andKhan, (2000) L. cuprina andHassan et al,(2019) for Musca domestica.…”
Section: Discussionsupporting
confidence: 86%
“…On the other hand, gamma radiation affected the reproductive potential of different dipteran species and the sterility percent increased as the dose increased (Jahan et al,1998;Huda and Khan, 2000;Khan and Islam, 2006;Hassan et al,2019). So, the present study was performed to investigate the effect of different doses of gamma radiation (as a physical agent) on the reproductive potential of the blowfly, C. albiceps.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation